Ion beam transport: modelling and experimental measurements on a large negative ion source in view of the ITER heating neutral beam. (11th November 2016) - Veltri, P.; Sartori, E.; Agostinetti, P.; Aprile, D.; Brombin, M.; Chitarin, G.; Fonnesu, N.; Ikeda, K.; Kisaki, M.; Nakano, H.; Pimazzoni, A.; Tsumori, K.; et al.
Abstract: Neutral beam injectors are among the most important methods of plasma heating in magnetic confinement fusion devices. The propagation of the negative ions, prior to their conversion into neutrals, is of fundamental importance in determining the properties of the beam, such as its aiming and focusing at long-distances, so as to deposit the beam power in the proper position inside the confined plasma, as well as to avoid interaction with the material surfaces along the beam path. The final design of the ITER Heating Neutral Beam prototype has been completed at Consorzio RFX (Padova, Italy), in the framework of a close collaboration with European, Japanese and Indian fusion research institutes. The physical and technical rationales on which the design is based were essentially driven by numerical modelling of the relevant physical processes, and the same models and codes will be useful to design the DEMO neutral beam injector in the near future. This contribution presents a benchmark study of the codes used for this purpose, by comparing their results against the measures performed in an existing large-power device, hosted at the National Institute for Fusion Science, Japan. In particular, the negative ion formation and acceleration are investigated. A satisfactory agreement was found between codes and experiments, leading to an improved understanding of beam transport dynamics. The interpretation of the discrepancies identified in previous works, possibly related to the non-uniformity of the extracted negative ion current, is also presented.